Body As Media In Action Drawing Titled Metamorposer 6 - Luna Dian Setya Avissa; Agus Purwantoro (Institut Seni Indonesia Denpasar, 2018)
The artist observe her own life and choose metamorphosis of butterfly as a metaphor. The idea of a visual artwork entitled Metamorposer 6 particulary taken from the phase of metamorphosis called pupa stage, the work is about the artist who needs to be alone like a caterpillar in a chrysalis to contemplate her selfish side and the desire to devote to her family. Action of drawing as a form of art is chosen to represent the process of making a distance with the surrounding environment and building a space of seclusion. The artist tried to improve her way of creation through media exploration, she also make some conventional result-oriented drawing on the transparant media prior to her action drawing. The idea is communicated not only through strokes of pigment on the transparent panel but also through a process that unifies the space, time and body as media in action drawing. The blank field on the panel is filled with drawings made analogously by the artist throuh manipulating the alkohol-based permanent marker with her right hand and the execution takes about 16 hours in total. The performance in this action drawing displays the drawing lines that slowly covered the body of the artist in a vitrine or transparent case constructed on a table. The present of the body in the action drawing as one of the media being compared with other previous works of notorious artist in an effort to conclude its meaning, function and experience.Seniman mengamati kehidupannya sendiri dan memilih metamorfosis kupu-kupu sebagai metafora. Ide karya seni visual yang berjudul Metamorposer 6 secara partikular berfokus pada fase metamorfosis yang disebut pupa, karya adalah tentang seniman yang perlu sendirian seperti ulat di dalam kepompong untuk merenungkan sisi egoisnya dan keinginan untuk berbakti kepada keluarganya . Action drawing sebagai sebuah bentuk seni dipilih untuk mewakili proses pembuatan jarak dengan lingkungan sekitar dan membangun ruang pengasingan. Sang seniman berusaha memperbaiki cara kreasinya melalui eksplorasi media, ia juga membuat beberapa gambar berorientasi hasil pada media transparan sebelum action drawing. Idenya dikomunikasikan tidak hanya melalui goresan pigmen pada panel transparan tetapi juga melalui proses yang menyatukan ruang, waktu dan tubuh sebagai media dalam aksi menggambar. Bidang kosong pada panel diisi dengan gambar yang dibuat secara analog oleh seniman yang memanipulasi marker permanen berbasis alkohol dengan tangan kanannya. Eksekusi karya memakan waktu sekitar 16 jam secara total. Seniman melalui action drawing menampilkan garis gambar yang perlahan-lahan menutupi tubuhnya yang dipajang dalam vitrine atau kotak transparan yang biasa untuk menyajikan benda seni. Kehadiran tubuh dalam action drawing sebagai salah satu media perlu dibandingkan dengan karya seniman terkenal lainnya yang berbasis aksi dan tubuh guna menemukan makna, fungsi dan menjabarkannya sebagai sebuah pengalaman.